Skeletal effects following developmental flame-retardant exposure are specific to sex and chemical class in the adult Wistar rat - Schkoda, Stacy; Horman, Brian; Witchey, Shannah K.; Jansson, Anton; Macari, Soraia; Patisaul, Heather B. (Frontiers in Toxicology, 2023)
Introduction: Accumulating evidence reveals that endocrine disrupting chemicals (EDCs) can disrupt aspects of metabolic programming, suggesting that skeletal development may be at risk, a possibility that is rarely examined. The commercial flame retardant (FR) mixture, Firemaster 550 (FM 550), has repeatedly been shown to negatively influence metabolic programming, raising concerns that skeletal integrity may consequently be impaired. We have previously shown that gestational and lactational exposure to 1,000 µg FM 550 negatively affected sex-specific skeletal traits in male, but not female, rats assessed at 6 months of age. Whether this outcome is primarily driven by the brominated (BFR) or organophosphate ester (OPFR) portions of the mixture or the effects persist to older ages is unknown. Materials and methods: To address this, in the present study, dams were orally exposed throughout gestation and lactation to either 1,000 μg BFR, 1,000 µg OPFR, or 2,000 µg FM 550. Offspring (n = 8/sex/exposure) were weaned at PND 21 and assessed for femoral cortical and trabecular bone parameters at 8 months of age by high-resolution X-ray micro-computed tomography (micro-CT). Serum levels of serotonin, osteocalcin, alkaline phosphatase, and calcium were quantified. Results: FM 550 affected both sexes, but the females were more appreciably impacted by the OPFRs, while the males were more vulnerable to the BFRs. Conclusion: Although sex specificity was expected due to the sexual dimorphic nature of skeletal physiology, the mechanisms accounting for the male- and female-specific phenotypes remain to be determined. Future work aims to clarify these unresolved issues.